Pengaruh Cairan Pendingin Terhadap Kekasaran Permukaan Benda Kerja Pada Proses Face Milling - Arya Rudi Nasution; Affandi .; Z. Fuadi (Rekayasa Material, Manufaktur dan Energi, 2020)
Coolant is one of the factors that affects the quality of the workpiece. The selection of coolant is useful to lower the surface roughness of the workpiece. In addition, coolant should be easily degradable in the environment so that the environment is not polluted. Example coconut oil is an oil that can be degraded in the environment. This research is aimed to observe the influence of coconut oil for cooling to the surface roughness obtained during face milling process. In the experimental tests, conventional milling machine was used and the milling tests were performed under various machining parameters, namely spindle rotational speed was 360 and 490 rpm, feeding speed was 60 mm/min and 70mm/min. Based on the result, the surface for spindle rotational speed of 360 rpm and feeding speed 60 mm/min was more rough than one in spindle rotational speed of 360 rpm and feeding speed 70 mm/min. Besides, the surface roughness for spindle rotational speed of 490 rpm and feeding speed of 60 mm/min was also more rough than one in spindle 490 rpm and 70 mm/min.